1978
DOI: 10.1111/j.1467-6494.1978.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Language and hand: The dimension of referential competence1

Abstract: Kinesic and verbal performance data were collected for two groups of women college seniors chosen to represent extremes in a type of verbal ability termed here referential competence. This ability is conceptualized in terms of degree of integration of symbolic and ikonic representation systems, i.e., the strength of the symbol-referent links in semantic memory. A criterion measure of referential competence was developed using deviation of color naming from word-reading times on the Stroop Color-Word test. Refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Bucci and Freedman (1978) have described a measure of verbal ability, specifically referential competence, which refers to the strength of object-to-word links in semantic memory. This ability is operationally defined by latencies in a Stroop color naming task, adjusted for individual differences in word reading speed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bucci and Freedman (1978) have described a measure of verbal ability, specifically referential competence, which refers to the strength of object-to-word links in semantic memory. This ability is operationally defined by latencies in a Stroop color naming task, adjusted for individual differences in word reading speed.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Mapping these observations onto Bucci and Freedman's (1978) model leads to elderly subjects being classified as having low referential competence, and young subjects as having high referential competence. (3) Bucci and Freedman's (1978) model can be extended to deal with descriptive and non-descriptive gestures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such code switching has been termed referential processing (Paivio, 1971(Paivio, , 1986 or referential activity (Bucci, 1984;Bucci & Freeman, 1978), and it is reflected most directly in picture-naming and word-imaging tasks. Referential processing is implicated as well in memory of pictures and words, symbolic comparisons, language comprehension, cognitive deficits after brain damage (e.g., Kosslyn, 1987;Thompson, Hall, & Sison, 1986), and other cognitive phenomena, and it raises important conceptual issues on which contemporary theories of mental representation differ.…”
mentioning
confidence: 99%
“…Thus, Baxter, Winters and Hammer (1968) showed that the more fluently a person could talk about some topic and the more thoroughly they knew the topic, the more complex their gestural expression was observed to be. Bucci and Freedman (1978) showed that persons who showed more creativity in language use when recounting episodes from their life of personal significance, were also more elaborate in their use of manual actions while speaking. Gullberg (1998) reported that the more fluent learners of a second language were, the more they employed gestures that expressed referential content of their discourse.…”
Section: Differentiation In Utterance Visible Action and Kinesic Compmentioning
confidence: 97%